Students Engagement in Classroom Teaching by Innovative Pedagogy: A desk-based Review of Existing Literature - Paudel, Min Raj; Shrestha , Nabin (JMC Research Journal, 2024)
The use of modern teaching methods in the social sciences classroom under higher levels of education is presently required to increase learning achievement through student participation. The pace of change in educational structures, curricula, teaching-learning activities, and learning outcomes should be able to keep up with all kinds of developments taking place in the world. Innovative is one of the newly developed approaches that can be used to increase students' active engagement, particularly in social science disciplines. A thorough literature search technique was employed to find the literature relevant to this study. The datasets up to 2024 were utilized for descriptive analyses of effective instructional techniques. The research-based articles and reports were used from digital and physical libraries. The easily accessible web search engine Google Scholar and other freely accessible databases such as Academia, ResearchGate, NAPJOL, JSTOR, ProQuest, and Elsevier were used. The findings indicate that innovative teaching methods promote the active participation of students through hands-on experiences. This approach significantly enhances learning outcomes in social science and helps for applying theories in real life. This technique promotes a more dynamic learning environment by encouraging teachers to adopt innovative and creative teaching methods, which in turn increases student engagement, motivation, and academic achievement. Integrating innovative pedagogies into activity-based instruction techniques empowers teachers to cultivate pupils' success, equipping them with essential skills for thriving in the 21st century.